Statement Of Retraction: Emotional Intelligence And Empathy: Predictors Of Counselors’ General Health (Academic Journal of Psychology and Counseling, 2024)
We, the editors and publishers, decided to retract the article entitled "Emotional Intelligence And Empathy: Predictors Of Counselors' General Health" with authors Peter Worlanyo Abomah (Department Of Psychology, Methodist University College, Ghana), Gladstone Agbakpe (Department Of Psychology, Methodist University College, Ghana), Cynthia Naa Lamiley Quaye (Department Of Psychology, Methodist University College, Ghana). We published the article in Volume 4 Issue 1 2023 (https://ejournal.uinsaid.ac.id/index.php/ajpc/article/view/7478). The authors were proven to have committed violations in the form of multiple submissions (https://scientific-publishing.webshop.elsevier.com/research-process/paper-retraction-meaning-and-main-reasons/). This article was also published in the International Journal of Natural Sciences: Current and Future Research Trends Volume 20 Issue 1 page 1-17 (https://ijnscfrtjournal.isrra.org/index.php/Natural_Sciences_Journal/article/view/1200). The authors have been informed about the retraction of the article. The retracted articles will remain online, but they will be digitally watermarked on each page as ‘Retracted’.